Experimental study on flow around immersed objects - Lailatul Jalilah, Kaharudin (2014)
It is well known that when fluid flows around an object, the object will experience a force due to the interaction between the object and the fluid surrounding it. This study was conducted in an open channel using three different types of immersed objects (circular-shaped, rectangular-shaped, square-shaped) and was divided into two parts. The first part was on the investigation of wake length that results due to different immersed object shapes and fluid flow velocities. The experiments were carried out at different flow rates ranging from 2 L/s to 14 L/s and the corresponding wake lengths were measured. The results show that the wake length increases as the velocity increases. The second part of the study was on the investigation of the resultant drag force on the immersed objects during different combinations of object shapes and fluid flow velocities. Based on the experimental data, the Reynolds number for each immersed object was calculated and the drag coefficient of each immersed object was obtained from graphs and tables in established publications. It was found that the Reynolds numbers for both square and circular shape of the immersed objects were similar due to the frontal area of the objects that were taken into account in the calculations. The resultant drag force was calculated based on the drag coefficient obtained. From the results, the flowing water exerted the highest drag force on the immersed object that was rectangular-shaped compared to the other two shapes that was investigated. This is the effect of different drag coefficient values that are in turn based on the respective Reynolds number and object shape. Another finding was that when the velocity and drag coefficient were increased, the drag force values also increased.